Genomic and phenotypic characterisation of Pseudomonas aeruginosa isolates from canine otitis externa reveals high-risk sequence types identical to those found in human nosocomial infections - Secker, Bailey; Shaw, Stephen; Hobley, Laura; Atterbury, Robert J. (Frontiers in Microbiology, 2025)
IntroductionCanine otitis externa (OE) is a frequently-diagnosed condition in veterinary practices worldwide. Pseudomonas aeruginosa is commonly associated with chronic and recalcitrant canine OE, but studies with detailed genomic and phenotypic characterisation of clinical isolates are lacking.MethodsPseudomonas aeruginosa canine OE isolates (n = 253) were collected from different geographical locations in Europe and characterised with respect to antimicrobial resistance and biofilm formation. A subset (n = 35) were genome sequenced then characterised with respect to diversity, and complement of virulence, antimicrobial resistance, and biofilm-associated genes.ResultsGenome-sequenced P. aeruginosa strains were distributed among phylogroups, showing no obvious clonality. However, two isolates belonged to ST111 and ST244 respectively,—MLST sequence types associated with AMR nosocomial infections in humans. Resistance to fluoroquinolones was detected in 25% of isolates, and multidrug resistance detected in 1.6%, though this did not always correlate with the presence of antimicrobial resistance genes. Additionally, 82% of isolates were characterised as forming strong biofilms.DiscussionFor the first time, this study has characterised a large multinational collection of P. aeruginosa isolates from canine otitis with a combination of whole genome sequencing, phenotypic screening and bioinformatic analysis. These strains did not cluster together based on genomic diversity or virulence gene complement, supporting their likely environmental origin. However, the identification of ST111 and ST244, important ‘high-risk’ sequence types, could suggest potential spread between humans and dogs. Furthermore, we found that most strains were formed strong biofilms, and exhibited a significant level of resistance towards critically important antimicrobials. These findings could assist in the selection of appropriate treatments for canine OE as well as possibly identifying one health risks of these infections for cohabiting pets and humans.